2010
DOI: 10.1073/pnas.0914069107
|View full text |Cite
|
Sign up to set email alerts
|

Programmable matter by folding

Abstract: Programmable matter is a material whose properties can be programmed to achieve specific shapes or stiffnesses upon command. This concept requires constituent elements to interact and rearrange intelligently in order to meet the goal. This paper considers achieving programmable sheets that can form themselves in different shapes autonomously by folding. Past approaches to creating transforming machines have been limited by the small feature sizes, the large number of components, and the associated complexity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
474
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 577 publications
(480 citation statements)
references
References 28 publications
1
474
0
Order By: Relevance
“…Likewise, photomechanical systems require specific light-sensitive liquid crystalline polymers [1][2][3] , and polyurethanes rely on the combination of hard and soft polymeric domains to change shape under external stimulus. Other shape-changing synthetic systems have been created, including, for example, sheets with origami-like folding properties produced either by lithographically depositing multiple layers of different materials [5][6][7] or by introducing electrically accessible actuators in specific regions of the sheet 8 . While the resulting heterogeneous structures lead to unique autonomous folding effects, the isotropic nature of the materials involved and the uniform thickness of the layers produced limit the shape changes to bending movements.…”
mentioning
confidence: 99%
“…Likewise, photomechanical systems require specific light-sensitive liquid crystalline polymers [1][2][3] , and polyurethanes rely on the combination of hard and soft polymeric domains to change shape under external stimulus. Other shape-changing synthetic systems have been created, including, for example, sheets with origami-like folding properties produced either by lithographically depositing multiple layers of different materials [5][6][7] or by introducing electrically accessible actuators in specific regions of the sheet 8 . While the resulting heterogeneous structures lead to unique autonomous folding effects, the isotropic nature of the materials involved and the uniform thickness of the layers produced limit the shape changes to bending movements.…”
mentioning
confidence: 99%
“…It will be shown that the system defined by Eqs. (13)(14)(15)(16)) has a number of equilibria which are both stable and unstable and may be connected through paths in the phase space of the problem. One type of path is the heteroclinic connection which requires the stable and unstable manifolds of two unstable equilibria to be connected.…”
Section: Approximate Heteroclinic Connection and Controlmentioning
confidence: 99%
“…Some applications of reconfiguring smart structures are also emerging to improve the aerodynamic and aeroelastic performance of aircraft [15]. Recently a new smart structure concept for self-folding origami has been presented, which can fold itself through embedded electronics into a desired shape [16]. A crawling robot that can fold itself was developed to demonstrate the application of this technique to the fabrication of reconfigurable machines [17].…”
Section: Introductionmentioning
confidence: 99%
“…Of the many methods for fabricating such structures, few are compatible with the highest-performance classes of electronic materials, such as monocrystalline inorganic semiconductors, and only a subset of these can operate at high speeds, across length scales, from centimeters to nanometers. For example, although approaches (36)(37)(38)(39) that rely on self-actuating materials for programmable shape changes provide access to a wide range of 3D geometries, they apply only to certain types of materials [e.g., gels (36,37), liquid crystal elastomers (39), and shape memory alloys (38)], generally not directly relevant to high-quality electronics, optoelectronics, or photonics. Techniques that exploit bending/folding of thin plates via the action of residual stresses or capillary effects are, by contrast, naturally compatible with these modern planar technologies, but they are currently most well developed only for certain classes of hollow polyhedral or cylindrical geometries (1,10,(40)(41)(42)(43)(44).…”
mentioning
confidence: 99%